Design and development of a predator sumo robot - Tham, Kwong Mun. (2008)
This project is to design and develop a Sumo Robot that is capable of competing in a ring arena with diameter of 1540mm. The robot's main task is to push its opponents out of the ring arena without itself being pushed out or disqualified.